Impact of esophageal myotomy length during laparoscopic Heller myotomy for achalasia type II - Rosales-Vazquez, Cristopher; Camacho-Cervantes, Giova; Verdugo-Salazar, Carlos I.; Gomez-Arenas, Samuel R.; Nacud-Bezies, Yamir A. (International Surgery Journal, 2025)
Background: Type II achalasia (Ach2) is the most prevalent esophageal motility disorder. Current guidelines recommend laparoscopic Heller myotomy (LHM) as a standard treatment, but the optimal esophageal myotomy length remains under investigation. Methods: A retrospective cohort study was conducted from 2018 to 2023 at a tertiary care center. Consecutive Ach2 patients undergoing LHM were included. Patients were grouped based on myotomy length (short vs long). Outcomes assessed included operative time, adverse events, Eckardt scores at 6 and 12 months, and treatment success. Results: Fifty-one patients were analyzed. Eckardt score at 6 months was significantly lower in the long myotomy group compared to the short group (1.2±1.1 vs 0.6±1.2, p=0.023). At 12 months, Eckardt scores were also significantly better in the long myotomy group (1.8±1.7 vs 0.9±1.2, p=0.033). Treatment success at 12 months was 92% in the short group and 100% in the long group, but it was not statistically significant (p=0.191). Conclusions: LHM provides high clinical success in Ach2 patients. While treatment success at 12 months was similar between groups, longer myotomy was associated with significantly lower Eckardt scores at both 6 and 12 months. These findings suggest a potential benefit in symptom control with longer myotomy, supporting further prospective studies to determine its clinical utility.